Improvisational Interactivity - Moving Beneath the ICE. - Smith , Stephen; Lloyd, Rebecca (Université d'Ottawa | University of Ottawa, 2022)
The relationally oriented, interactive approach to Creativity Imagination Education (ICE) featured in this chapter prioritizes motion-sensitivity and the felt kinaesthetic sense. As an alternative to cognitively construed conceptions of creativity, we provide a series of student friendly inter-activities that invite you to experience the bodily feelings and energetic flows of improvisational creativity firsthand. Inspired by research conducted with improvisational experts in salsa dance, push-hands tai chi, acro-yoga, tap dance, and equestrian arts, we attune to the sensorial and relational depths beneath the educational "ICEberg." While pathways may certainly be created from the simple mimetic practices featured in this chapter to more physically skillful games and partnered disciplines, we trust that focusing on everyday interactions with one another will inspire you to consider how teaching and learning can be enhanced by moving interactively and improvisationally with others.
Keywords: creative imagination education; motion-sensitivity